Barbarians on the Coins of Trajan Decius (249–251): - Kluczek, Agata (Studia Ceranea, 2020)
During Trajan Decius’s reign (249–251) in a number of provincial mints – Alexandria, Caesarea Maritima, Magnesia ad Sipylum and Nicomedia – coins were issued featuring the theme of the barbarian (an enemy or a captive) in reverse iconography. In this article, I discuss these coins, considering them in the context of the iconographic tradition and the activity of the particular mints during Decius’s reign, and also in relation to the ideology of victory and the dynastic ideology. They are interesting especially because the theme of the barbarian was not utilised in the parallel imperial coinage. Nevertheless, its presence in provincial coinage is also of a marginal nature. Moreover, the end of Decius’s reign also coincided with a time-related hiatus in the use of the theme in provincial coinage.